Comparative Evaluation in Intense Pulsed Light Therapy Combined with or without Meibomian Gland Expression for the Treatment of Meibomian Gland Dysfunction. (3rd August 2021) - Chen, Yiqin; Li, Junhua; Wu, Yue; Lin, Xiaolei; Deng, Xiaohui; Yun-e, Zhao
ABSTRACT: Objective: To determine whether the combination of meibomian gland expression (MGX) with intense-pulsed light (IPL) has a better efficacy to treat meibomian gland dysfunction (MGD) than IPL alone. Methods: One hundred patients with MGD were randomly divided into three groups: MGX, IPL, and IPL+ MGX. Clinical parameters included the Ocular Surface Disease Index (OSDI), tear meniscus height (TMH), noninvasive keratograph tear breakup time (NIBUT), redness, meibomian gland dropout, tear breakup time (TBUT), corneal fluorescent staining (CFS), eyelid margin score, meibomian gland secretion function, and Schirmer I tests were collected before treatment and at 1 and 3 months after treatment. Compare the indexes of each group before and after treatment and also compare the differences of each group on follow-up. Results: Compared to the baseline, OSDI, TBUT, and meibomian gland secretion function in IPL group improved throughout the follow-up period (all P < .05) and part of the meibomian gland secretion function increased continuously. OSDI, TBUT, lower eyelid margin scores, and meibomian gland secretion function in IPL + MGX group improved at the both follow-up visits (all P < .05), and continued improvement in meibomian gland secretion function can be observed. Lower meibomian gland dropout and CFS reduced at 1 month and 3 months respectively in IPL ± MGX group ( P = .001, P = .001).Compared to IPL group, only CFS has reduction in IPL + MGX group at 1-month ( P < .001), CFS, upper and lower MGYCS were improved at the 3 months ( P = .037, P = .014, P = .049). Conclusions: MGX may have synergistic effect when combined with IPL therapy, and the effect can last at least 3 months.